Effect of competence, discipline and work facilities on employee performance: (survey at PT. Perkebunan Nusantara V Sei Pagar Palm Oil Mill) - Rina Sundari; Arman Arman; Adi Setiawan (STIE Bangkinang Publishing, 2022)
This study aims to identify the effect of competence, discipline and work facilities on employee performance at the PT. Perkebunan Nusantara V Sei Pagar. The analysis used in this research is a multiple linear analysis with a total of 121 respondents. Hypothesis testing was carried out by means of a simultaneous test (F test) and a partial test (t test). Based on the research results, it can be concluded that simultaneously and partially competence, discipline and work facilities affect employee performance. The closeness of the bond between the independent variable and the dependent variable is a very strong relationship with the dependent variable and has a contribution of 66.0% to the dependent variable. On the other hand, the remaining 34.0% is influenced by other variables not listed in this research.